The Value of Voice A Conversation with Nick Couldry. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Nick Couldry, Professor of Media, Communications and Social Theory in the Department of Media and Communications at the London School of Economics. This wide-ranging conversation explores how the media can be used as a filter to examine power structures, political movements, economic interests, democracy and our evolving notion of culture. Prof. Couldry conveys the importance of voice and the challenge posed by media institutions that order the social, political, cultural, economic, and ethical dimensions of our li.